Moll Flanders - Defoe, Daniel, 1661?-1731 (Amersham : Transatlantic Press, 2012)
Moll Flanders is dealt a desperately poor hand, born in Newgate Prison to a convicted felon mother about to be transported to America for her crimes. Cast adrift in a harsh world, seduced at an early age, the ever-resourceful Moll learns to play the survival game with astuteness and irrepressible cunning. Her path is strewn with husbands and lovers, and when all else fails and destitution beckons, she turns to a life of crime to keep the wolf from the door. Moll is the ultimate self-starter, the great opportunist. If she falls from grace -- plummets might be more fitting -- then it's down to force of circumstance rather than indulgence ('the vice came in always at the Door of Necessity, not at the Door of Inclination'). Defoe's picaresque romp relates the history of one of literature's most engaging characters, a vital force of nature, a woman who strikes a proto-feminist blow as she uses all the means at her disposal to stay on top in a male-dominated world. -- from publisher.
Keywords: Children of prisoners -- Fiction; Women -- England -- Fiction; Prostitutes -- Fiction; Repentance -- Fiction; Criminals -- Fiction; English fiction; Virginia -- Fiction; London (England) -- Fiction